Non-prescribed use of psychoactive prescription drugs among drug-impaired drivers in Sweden. (1st April 2016) - Tjäderborn, Micaela; Jönsson, Anna K.; Sandström, Tatiana Zverkova; Ahlner, Johan; Hägg, Staffan
Highlights: Non-prescribed use of psychoactive prescription drugs among drug-impaired drivers was investigated. The prevalence was high and differed substantially across the investigated drugs. Factors are presented that may predict non-prescribed use of psychoactive prescription drugs. Abstract: Aims: To determine the prevalence of non-prescribed drug use among subjects suspected of drug-impaired driving with a psychoactive prescription drug, and to identify associated factors. Methods: Subjects investigated for drug-impaired driving in Sweden during 2006–2009 with a confirmed intake of diazepam, flunitrazepam, tramadol, zolpidem or zopiclone were identified using the Swedish Forensic Toxicology Database. Information on dispensed prescription drugs was retrieved from the Swedish Prescribed Drug Register. Non-prescribed use was our outcome, defined as a psychoactive prescription drug intake confirmed by toxicological analysis in a subject by whom it was not dispensed in the 12 months preceding the sampling. Prevalence proportions were calculated for each drug and logistic regression was used to identify associated factors. Results: In total, 2225 subjects were included. The median age (range) was 34 (15–80) years and 1864 (83.8%) subjects were male. Non-prescribed use was found in 1513 subjects (58.7%); for flunitrazepam 103 (76.3%), diazepam 1098 (74.1%), tramadol 192 (40.3%), zopiclone 60 (29.7%), and zolpidem 60 (21.2%) subjects, respectively. Younger age and multiple-substance use were associated with non-prescribed use, whereas ongoing treatment with other psychoactive drugs was negatively associated with non-prescribed use. Conclusions: Non-prescribed use of psychoactive prescription drugs was common in subjects suspected of drug-impaired driving and was more frequent for benzodiazepines and tramadol compared to zolpidem and zopiclone. The young and multi-substance users were more likely, whereas subjects with ongoing prescribed treatment with other psychoactive drugs were less likely, to use non-prescribed drugs.